Предмет: Математика,
автор: fefttrsyu90
4x²-12x+9=0
2x²-5x+2=0
10x²-6x+9=0
3x²-12x+9=0
6x²+5x+1=0
Ответы
Автор ответа:
0
Ответ:
х=1,5
х₁=2 x₂=0,5
х
х₁=3 x₂=1
х₁= x₂= -0,5
Пошаговое объяснение:
4x²-12x+9=0
D = b²-4ac
D = (-12)²-4*4*9=144-144=0
x = -
x = -
x = 1,5
2x²-5x+2=0
D = b²-4ac
D = (-5)²-4*2*2= 25-16=9
х₁=
х₁===2
х₂ =
х₂===0,5
10x²-6x+9=0
D = b²-4ac
D = (-6)²-4*9*10=36-360= -324
x
3x²-12x+9=0
D = b²-4ac
D = (-12)²-4*9*3=144-108=36
х₁=
x₁===3
х₂ =
x₂==1
6x²+5x+1=0
D = b²-4ac
D = 5²-4*1*6=25-24=1
х₁=
x₁===
х₂ =
x₂=== -0,5
Похожие вопросы
Предмет: Английский язык,
автор: троечиница
Предмет: Английский язык,
автор: elya14
Предмет: Українська література,
автор: Муцкий
Предмет: Информатика,
автор: litva92hok
Предмет: Математика,
автор: nikidrooon